2021
DOI: 10.3390/plants10040655
|View full text |Cite
|
Sign up to set email alerts
|

Single-Molecule Long-Read Sequencing of Purslane (Portulaca oleracea) and Differential Gene Expression Related with Biosynthesis of Unsaturated Fatty Acids

Abstract: This study aimed to obtain the full-length transcriptome of purslane (Portulaca oleracea); assorted plant samples were used for single-molecule real-time (SMRT) sequencing. Based on SMRT, functional annotation of transcripts, transcript factors (TFs) analysis, simple sequence repeat analysis and long non-coding RNAs (LncRNAs) prediction were accomplished. Total 15.33-GB reads were produced; with 9,350,222 subreads and the average length of subreads, 1640 bp was counted. With 99.99% accuracy, after clustering, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 65 publications
1
5
0
Order By: Relevance
“…In addition, both ω-3 alpha-linolenic acid and ω-6 linoleic acid are unsaturated fatty acids and the unsaturation level of plants' ability is used to maintain or regulate membrane fluidity, which was positively related with plant-tolerance to abiotic stress [31]. These findings are in line with those of our previous studies, in which 94 genes were identified and participate in the pathway of biosynthesis of unsaturated fatty acids and FAD2 family genes regulated for unsaturation of fatty acid composition and played an important role in ω-3 and ω-6 fatty acid desaturase to increase stress tolerance [10]. Some plants have fatty acid desaturations that regulate chloroplast fluidity and increase tolerance mechanisms in specific cultivars.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In addition, both ω-3 alpha-linolenic acid and ω-6 linoleic acid are unsaturated fatty acids and the unsaturation level of plants' ability is used to maintain or regulate membrane fluidity, which was positively related with plant-tolerance to abiotic stress [31]. These findings are in line with those of our previous studies, in which 94 genes were identified and participate in the pathway of biosynthesis of unsaturated fatty acids and FAD2 family genes regulated for unsaturation of fatty acid composition and played an important role in ω-3 and ω-6 fatty acid desaturase to increase stress tolerance [10]. Some plants have fatty acid desaturations that regulate chloroplast fluidity and increase tolerance mechanisms in specific cultivars.…”
Section: Discussionsupporting
confidence: 90%
“…The cellular antioxidant system, composed of superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT), is essential for limiting ROS generation and protecting plants against cold stressors and abiotic conditions [8]. However, it is known that linoleic and linolenic acids modulate the plant's defense mechanism against several abiotic stressors [9][10][11]. Linoleic and alpha-linolenic acid are the most important unsaturated fatty acids [10] that have been effective against a variety of disorders, including cancer [12] and cardiovascular disease [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to synthesizing ω-3 fatty acids, purslane also produces ω-6-fatty acids. Du et al (2021) identified 94 genes involved in the biosynthetic pathway of unsaturated fatty acids. Three genes encoding ω-6 fatty acid desaturases viz.…”
Section: Genetics Of Phytochemical Nutritional and Stress-resilient Traitsmentioning
confidence: 99%
“…The study showed that three important genes, namely, Ribosomal protein S15A (RPS15A), Ribosomal protein L2 (RPL2), and ω-6-fatty acid desaturase 2 (FAD2) were induced at higher levels following rewatering/recovery of purslane, suggesting their important roles in imparting stress tolerance. FAD2 and stearoyl-acyl-carrierprotein desaturase (SAD) are also important genes involved in ω-3 fatty acid biosynthesis, and there differential expression is reported in stem and leaves of P. oleracea (Du et al, 2021). C4/CAM switching is one of the most important mechanisms reported from purslane in response to the differences in environmental conditions.…”
Section: Genetics Of Phytochemical Nutritional and Stress-resilient Traitsmentioning
confidence: 99%